Pengaruh Pemberian Obat Anti Tuberkulosisi (OAT) Terhadap Jumlah Trombosit pada Pasien TB Paru di BKPM Purwokerto: The Effect of Anti Tuberkulosis Drug (OAT) Towards the Number of Pulmonary TB Patients at BKPM Purwokerto - Ika Wulan Nuri Anggreani; Tantri Analisawati Sudarsono; Dita Pratiwi Kusuma Wardani; Minto Rahaju (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Pulmonary tuberculosis (TB) is an infection of the lungs characterized by pulmonary infiltrates and the formation of caseous granulomas, fibrosis, and cavities. It can be caused by the risk of transmission of the acid-fast bacillus Mycobacterium tuberculosis. One supportive treatment for pulmonary TB is the administration of anti-tuberculosis drugs (OAT). The content of rifampicin in the anti-tuberculosis drug can cause side effects of hemorrhagic disorders, namely thrombocytopenia. This study aims to determine the effect of giving OAT on platelet counts in TB patients in treatment phases of 0, 2, and 6 months at BKPM Purwokerto (Balai Kesehatan Paru Masyarakat). This was a type of analytic observational study with a cross-sectional design. Patients with pulmonary TB in treatment phase 0 were 15 at two months and 15 at six months in this study. Sampling was carried out by purposive sampling with inclusion and exclusion criteria. From this analysis, it is known that the data used the one-way ANOVA test. The results obtained have a p-value of 0.101 (p 0.05), so it can be concluded that there is no effect of the administration of OAT on platelet counts in TB patients in the treatment phases of 0, 2, and 6 months.